Enabling Efficient Consumer Revocation for Identity based Cloud Storage Auditing for Shared Big Data Records - Bohara, Ayushi P; A, Chethan; B, Haripriya; Biradar, Arun (International Journal of Computer Sciences and Engineering, 2025)
Cloud storage auditing schemes for shared facts refer with checking the integrity of cloud facts shared via a collection of customers.User revocation is commonly supported in such schemes, as customers may be issue to organization or may misbehave.Previously, the computational overhead for consumer revocation in such schemes was linear with the entire quantity of document blocks possessed by a revoked consumer. In this paper, we advise a singular storage auditing scheme that achieves consumer revocation unbiased of the full variety of file blocks possessed via the revoked consumer in the cloud. This is carried out through exploring a novel approach for key era and a brand new personal key replace method. By using this approach, we realize consumer revocation via simply updating the non revoked customers’ personal keys rather than authenticators of the revoked consumer. The integrity auditing of the revoked consumer’s data can nonetheless be efficaciously achieved when the authenticators aren't updated. Meanwhile, the proposed scheme is based totally on identification-base cryptography, which gets rid of the complex certificate control in conventional Public Key Infrastructure (PKI) structures. the safety and efficiency of the proposed scheme are confirmed through both evaluation and experimental consequences.